Scales of memory constitutional justice and historical evil - Collings, Justin (Oxford comparative constitutionalism., 2021)
This book explores the relationship between constitutional interpretation and the memory of historical evil. Specifically, it examines how the constitutional courts of the United States, Germany, and South Africa have grappled, respectively, with the legacies of slavery, Nazism, and apartheid.